2022
DOI: 10.3390/vaccines10050798
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Homologous and Heterologous Prime–Boost Immunization with COVID-19 Vaccine: Systematic Review and Meta-Analysis

Abstract: A prime–boost strategy of COVID-19 vaccines brings hope to limit the spread of SARS-CoV-2, while the immunogenicity of the vaccines is waning over time. Whether a booster dose of vaccine is needed has become a widely controversial issue. However, no published meta-analysis has focused on the issue. Therefore, this study assessed the immunogenicity and safety of the different combinations of prime–boost vaccinations. Electronic databases including PubMed, the Cochrane Library, Embase, medRxiv, Wanfang and CNKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 61 publications
4
32
1
Order By: Relevance
“…Regarding the impact of booster vaccine doses on humoral immunity, we showed that heterologous mRNA vaccine boosters elicited higher levels of anti-RBD total antibodies than homologous schedules, as previously reported. 20,21 However, a similar analysis could not be performed for NtAb due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of booster vaccine doses on humoral immunity, we showed that heterologous mRNA vaccine boosters elicited higher levels of anti-RBD total antibodies than homologous schedules, as previously reported. 20,21 However, a similar analysis could not be performed for NtAb due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…There were two strategies for using the booster dose vaccine: homologous (using the same vaccine platform) and heterologous (using a different vaccine platform) when compared to the previous two doses of the vaccination. Several studies have found that heterologous vaccines outperform homologous vaccines in terms of higher antibody production and T-cell activation in both the general population and KTRs [ 22 , 23 , 38 ]. The rate of seroconversion can be achieved in 60–70% of primary non-responders with a heterologous booster dose, leaving 20–25% of KTRs with no seroconversion after receiving a booster dose [ 15 , 16 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A booster dose of the vaccination was used to increase antibody levels with the hope that it would reduce incidence and severity of breakthrough infection. Most studies found that a booster dose can significantly increase antibody levels, especially heterologous vaccine platform [ 22 , 23 , 24 , 25 ], but clinical outcomes were not reported. Almost all studies reported results of an mRNA vaccine.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 30 , 32 , 33 , 34 This increase was consistent with the rise of binding (median fold increase = 26.8; IQR = 13.6–51.7) 35 , 36 , 37 and neutralizing antibodies (median fold increase = 27.3; IQR = 10.2–52.7). 18 , 19 , 38 , 39 , 40 , 41 However, a waning of protection against symptomatic diseases was rapidly observed 8–14 weeks after the booster (median VE = 37.9%; IQR = 24.6%–45.1%). 7 , 30 , 33 Although protection against severe COVID‐19 remains higher, the Center for Disease Control and Prevention reported that after receiving both 2 and 3 doses, the VE was lower during the Omicron‐predominant than during the Delta‐predominant period at all time points evaluated.…”
Section: Introductionmentioning
confidence: 99%